(untitled) (Revista Contexto & Educação, 2023)
From the perspective of inclusive education, there is a need for educational institutions to prepare their teachers to handle this demand and, in higher education contexts, the gap in teacher training was more accentuated by the lack of knowledge on how to deal with people with disabilities and/or with specific educational needs. The objective was to describe the experience of continuing education of university professors, from the perspective of inclusive education. This is a descriptive, qualitative study, an experience report on the continuing education of teachers in higher education, from the perspective of inclusive education, experiences in the socio-historical and cultural context of programs/events developed with the participation of the authors. The experiences took place at a private university in Northeastern Brazil, from 2013 to 2019. Two experiences are presented: a psychopedagogical support service and a professional development program for teachers. From the beginning to the end of each course, module or workshop, strategies of mediation were decisive for the promotion of inclusive educational debate, providing moments for development of collaborative actions fostering protagonism and autonomy of the participants. The continuing education practices mediated by the authors and reported here aimed at the teachers’ protagonism in collaborative construction of solutions for different situations inherent to the pedagogical praxis of the participants.